2019
DOI: 10.1080/15384047.2019.1583533
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic value of PDL1 protein expression in breast cancer patients in neoadjuvant setting

Abstract: Objective: Programmed death-ligand-1 (PDL1) is a molecule involved in immune evasion in various kinds of tumors. Here, we aim to determine whether the expression of PDL1 protein is related to the response of patients to neoadjuvant therapy and survival outcome. Methods: Immunohistochemistry (IHC) was performed on paraffin-embedded tumor samples from core needle biopsy before neoadjuvant therapy (NAT). Univariate and multivariate logistic regression were used to analyze the associations between PDL1 protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
2
19
0
2
Order By: Relevance
“…In our study, G5 response to NACT in breast cancer was significantly associated with TCs PD-L1 positivity in pretreatment biopsies both in the total breast cancer population and in luminal subtype. Similar to other studies that used IHC technology, PD-L1 protein expression in TCs was found to be a predictive biomarker of pCR both in hormone receptor-positive patients and all 94 locally advanced breast cancer patients treated with NACT(with paclitaxel plus cisplatin weekly regimens, which was not the preferred therapy) by both univariate and multivariate logistic regression analysis [27]. However, the predictive value of PTLCs PD-L1 expression for pCR was not analyzed, and the molecular subtypes and nodal status were not included in the analysis, which were included in our study.…”
Section: Discussionsupporting
confidence: 65%
“…In our study, G5 response to NACT in breast cancer was significantly associated with TCs PD-L1 positivity in pretreatment biopsies both in the total breast cancer population and in luminal subtype. Similar to other studies that used IHC technology, PD-L1 protein expression in TCs was found to be a predictive biomarker of pCR both in hormone receptor-positive patients and all 94 locally advanced breast cancer patients treated with NACT(with paclitaxel plus cisplatin weekly regimens, which was not the preferred therapy) by both univariate and multivariate logistic regression analysis [27]. However, the predictive value of PTLCs PD-L1 expression for pCR was not analyzed, and the molecular subtypes and nodal status were not included in the analysis, which were included in our study.…”
Section: Discussionsupporting
confidence: 65%
“…On contrary, PD-L1 expression has been reported to be associated with worse prognosis of triple negative breast cancer patients, which counteract effect of tumor-infiltrating lymphocytes [10]. Response of BC patients to neoadjuvant therapy and survival outcome indicated that PD-L1 predicted better rate of pathological complete response (pCR) [26]. In addition, PD-1/PD-L1 correlated genes such as CD5, CD74, CD96 and CD226 were also related with prognosis of BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal microRNAs (miRNAs), which are transferred by EVs, are promising and reliable tools for cancer diagnosis and clinical application [18]. PD-L1 overexpression has been examined as a prognostic factor in diverse cancers including lung cancer [19], gastric cancer [20], ovarian cancer [21], breast cancer [22], prostate cancer [23], bladder cancer [24], cervical cancer [25], cholangiocarcinoma [26], colorectal cancer [27], nasopharyngeal carcinoma [28], diffuse large B-cell lymphoma [29], pancreatic cancer [30], soft-tissue sarcoma [31], renal cell carcinoma [32], and head and neck squamous cell carcinoma [33]. In addition, in patients with melanoma, exosomal PD-L1 is an indicator of immune activation early after the initiation of treatment with immune checkpoint inhibitors (ICIs) and is associated with clinical response to ICIs [34].…”
Section: Introductionmentioning
confidence: 99%